2010
DOI: 10.1186/gb-2010-11-2-r21
|View full text |Cite
|
Sign up to set email alerts
|

Immunity and other defenses in pea aphids, Acyrthosiphon pisum

Abstract: The genome of the pea aphid Acyrthosiphon pisum lacks genes thought to be crucial in other insects for recognition, signaling and killing of microbes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
494
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(520 citation statements)
references
References 138 publications
22
494
3
1
Order By: Relevance
“…Aphids also lack known antimicrobial peptides that control endosymbionts in other insects (Gerardo et al. 2010), which may enable some endosymbionts to increase in abundance under stressful conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Aphids also lack known antimicrobial peptides that control endosymbionts in other insects (Gerardo et al. 2010), which may enable some endosymbionts to increase in abundance under stressful conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The study identified many D. noxia gut genes, including glutathione s-transferases and carboxypeptidases, involved in insect digestion and detoxification in insects (ffrench Constant et al 2000;Gerardo et al 2010). Glutathione s-transferases are known to detoxify reactive oxygen species related to plant stress in many arthropods (Ramsey et al 2010) whereas carboxypeptidases are basically involved in insect digestion (Bown and Gatehouse, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The recent sequencing of the pea aphid genome revealed an even more reduced immune gene repertoire than honeybees (Gerardo et al, 2010). Pea aphids lack a central immune pathway and all known antibacterial peptides (although they do have a relatively uncommon class of potentially antifungal peptides).…”
Section: Hypothesis-targeted Comparative Sequencingmentioning
confidence: 99%
“…Aphids can harbor several species of intracellular mutualistic bacteria. These mutualists can produce needed amino acids (Douglas, 1998) and can protect their hosts against parasites and other environmental stressors (reviewed in Gerardo et al, 2010). Researchers have hypothesized that aphids may lack these immune components because they are intimately dependent on bacterial symbionts for survival (Gerardo et al, 2010).…”
Section: Hypothesis-targeted Comparative Sequencingmentioning
confidence: 99%